Brand Experience On Consumer Satisfaction Purchasing Mobile Legend Virtual Game Items A Literature Review - Mario Andreas Ginting; Rusdiono Rusdiono; Moudy Fitria Respati; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (Harmony Management: International Journal of Management Science and Business, 2024)
The purpose of the research is to find out Brand Experience in analyzing Consumer Satisfaction for the purchase of Virtual Items in the Mobile Legend game. The method in writing this article, literature review plays an important role in formulating research ideas, understanding previous findings related to the topic raised, and identifying gaps in existing knowledge. Systematic literature reviews (SLRs) were conducted in two well-known databases, Science Direct and Scopus. After applying the inclusion and exclusion criteria, 1,498 out of 2,038 articles were considered relevant. Afterwards, these papers were carefully examined to produce an in-depth analysis of the subject. In the end, 12 papers were selected for in-depth examination in this study. Based on data from SLR articles written between 2021 and 2024. The research methodology used in this paper includes descriptive analysis and bibliographic analysis. The results of the article are known that Brand experience plays a very important role in increasing consumer satisfaction in purchasing Mobile Legends virtual game items. By creating a positive and consistent experience, developers can build strong relationships with players and encourage them to become loyal customers.